Bortezomib-based induction therapy with high or low-dose dexamethasone in newly diagnosed, transplant-eligible multiple myeloma - Mai, Elias K.; Bertsch, Uta; Schlenzka, Jana; Hillengaß, Jens; Raab, Marc-Steffen; Merz, Maximilian; Bärtsch, Marc-Andrea; Jauch, Anna; Hose, Dirk; Goldschmidt, Hartmut (Leukemia, 2019)
Brief Communication